2021
DOI: 10.1002/asi.24601
|View full text |Cite
|
Sign up to set email alerts
|

A comparative mixed methods study on health information seeking among US‐born/US‐dwelling, Korean‐born/US‐dwelling, and Korean‐born/Korean‐dwelling mothers

Abstract: More knowledge and a better understanding of health information seeking are necessary, especially in these unprecedented times due to the COVID‐19 pandemic. Using Sonnenwald's theoretical concept of information horizons, this study aimed to uncover patterns in mothers' source preferences related to their children's health. Online surveys were completed by 851 mothers (255 US‐born/US‐dwelling, 300 Korean‐born/US‐dwelling, and 296 Korean‐born/Korean‐dwelling), and supplementary in‐depth interviews with 24 mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…Information source preference research is primarily based on this theory to construct a holistic picture of a group's information source horizon. This study found that the information horizon theory, after the development of Sonnenwald (1999) and Savolainen and Kari (2004), could effectively understand people's information-seeking behavior and source preferences, and it would have a greater potential for future research on information-seeking behavior (Lee and Smith, 2022). However, as a core theory of information source preference research and a theory of the field itself, it still has insufficient application in the existing studies, with only 6.47% of studies applying information horizon theory.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Information source preference research is primarily based on this theory to construct a holistic picture of a group's information source horizon. This study found that the information horizon theory, after the development of Sonnenwald (1999) and Savolainen and Kari (2004), could effectively understand people's information-seeking behavior and source preferences, and it would have a greater potential for future research on information-seeking behavior (Lee and Smith, 2022). However, as a core theory of information source preference research and a theory of the field itself, it still has insufficient application in the existing studies, with only 6.47% of studies applying information horizon theory.…”
Section: Discussionmentioning
confidence: 90%
“…For example, Savolainen (2010) identified 22 potential information sources when home buyers seek information based on the information horizon theory and summarized the criteria of information source preferences such as the content of information, accessibility, usability, user characteristics and situation. Lee and Smith (2022) constructed the information source horizons of three groups of mothers in different regions seeking health information for their children based on the information horizon theory and compared the differences in the prioritization of information sources among the three groups. Information poverty theory provides a basis for exploring explanations of the information source preferences of specific populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media, such as forums, microblogging, and social networking, are Internet‐based applications built on the technological and ideological foundations of Web 2.0 that offer real‐time information and can significantly influence people's attitudes, beliefs, and decisions (Chipidza & Yan, 2022; Lee & Smith, 2022; Varathan et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social media platforms have greatly improved accessibility to public health information, emotional support, and surveillance, and have influenced health policy development (Chang et al, 2021; Lee & Smith, 2022). Public health systems have adopted social media worldwide to increase awareness, communicate health interventions, and serve as a vital surveillance tool (Kass‐Hout & Alhinnawi, 2013; Lyson et al, 2019; Stellefson et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%